MULTIDIMENSIONAL ASSESSMENT AS A METHOD OF RESEARCH OF THE TRAVEL MARKET SERVICES IN UKRAINE (International Journal of Innovative Technologies in Economy, 2018)
Conducted according to the financial statements and statistical analysis of financial and business tourism enterprises Ukraine suggests that the positioning of tourism enterprises is different segment of tourist flows, depending on the direction of travel. Use rating Tour operator based integrated assessment possible to identify three groups of tourism enterprises: high, medium and low integrated assessment and to evaluate differences in responses by the rating and ranking based on integrated assessment. The influence on the value of integrated assessment index synergistic effect of integrated marketing communications was the largest that can offer include the calculation of this indicator in analytical work of the marketing department of tour operators to improve the policy of integrated marketing communications business travel.